An Improved Current-Sensorless Method for Induction Motor Drives Applying Hysteresis Current Controller - Cuong Dinh Tran; Pavel Brandstetter; Minh Huu Chau Nguyen; Sang Dang Ho; Phuong Nhat Pham; Bach Hoang Dinh (IAES Indonesian Section, 2021)
A novel strategy based on the feed-forward field-oriented control (FOC) method is proposed for the Hysteresis Current technique to control the induction motor (IM) drive without current sensors (CSs). A control scheme is proposed to estimate stator currents from reference rotor flux, rotor flux angle, and state variables as a replacement for the feedback-signal of CSs used in the hysteresis current controller (HCC). Here the rotor flux angle component is extracted from the feed-forward FOC loop. MATLAB/Simulink is applied to implement the simulations under many different operating conditions. The simulation results demonstrated the feasibility of the proposed method to obtain high performance in controlling the IM drives without the current sensors.